Long-term results of total hip arthroplasty with «physiohip» trabecular-bionic stem - Kosiakov, Oleksandr; Buryanov Оleksandr; Bondar, Vitaliy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
More often short femoral components are used in Ukraine, including the trabecular bionic stem «Physiohip». Objective: to analyze the results of the total hip arthroplasty with this kind of stem, to determine the factors affecting the development of its aseptic loosening. Methods: we made retrospective analysis of 37 patients after total hip arthroplasty in 1 to 7 years follow-up. There were 25 men (68 %), women — 12 (32 %). The average age was 46 years old (from 28 tо 77). Operations were made at primary arthritis of the 3–4 stages, dysplastic arthritis 3–4 stages, and aseptic femoral head necrosis 3–4 degrees and femoral neck fractures. Functional results were assessed according to Harris Hip Score. Results: in 7 years after surgery excellent functional result was observed in 16 patients (43 %), in 9 patients (24 %) — good result, in 4 patients (11 %) there was satisfactory result, but in 8 cases (22 %) — failed result. The best functional results were at aseptic femoral head necrosis and idiopathic primary arthritis. Conclusions: Implantation of the trabecular bionic stem «Physiohip» h as i ts own a ccurate i ndications, t he o peration requires strict adherence to surgical techniques, and postoperative rehabilitation therapy must be carried out taking into account the individual characteristics of the patient. Factors that affected aseptic stem loosening were inaccurate choice of the stem size, inappropriate technique of stem implantation, osteoporosis and early active postoperative rehabilitation, especially in patients with high body mass index.